2011
DOI: 10.1016/j.ijsolstr.2011.03.010
|View full text |Cite
|
Sign up to set email alerts
|

On the limit velocity and buckling phenomena of axially moving orthotropic membranes and plates

Abstract: a b s t r a c tIn this paper, we consider the static stability problems of axially moving orthotropic membranes and plates. The study is motivated by paper production processes, as paper has a fiber structure which can be described as orthotropic on the macroscopic level. The moving web is modeled as an axially moving orthotropic plate. The original dynamic plate problem is reduced to a two-dimensional spectral problem for static stability analysis, and solved using analytical techniques. As a result, the mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…When the values of T 0 , c T and a T are set, the volatility parameter s T is obtained from Eq. (7). For the crack length process, when c ξ and a ξ are given, the shape parameter δ ξ is obtained from Eq.…”
Section: Results For Printing Pressesmentioning
confidence: 99%
See 1 more Smart Citation
“…When the values of T 0 , c T and a T are set, the volatility parameter s T is obtained from Eq. (7). For the crack length process, when c ξ and a ξ are given, the shape parameter δ ξ is obtained from Eq.…”
Section: Results For Printing Pressesmentioning
confidence: 99%
“…Studies of moving elastic strings were continued by Sack [2] and Archibald and Emslie [3], who were also the first published authors on axially moving materials in English. Later studies of axially moving materials concern, e.g., stability of traveling two-dimensional elastic [4,5], orthotropic [6,7] and viscoelastic [8,9] plates. Extensive literature reviews on the studies of axially moving materials can be found in [5,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies (see, e.g., [3][4][5][6][7][8], we have considered mathematical modelling of the mechanical aspects of the paper making process, using analytical and numerical approaches. The processing of paper, steel, fabric or rubber, and looping systems such as band saws and timing belts, all belong to the class of systems known as axially moving materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that the lack of web tension will result in a loss of stability of the moving web, which from the application A C C E P T E D M A N U S C R I P T viewpoint, disturbs the required smooth advancing of the web (see e.g. [4,3]). On the other hand, high tension may cause web breaks, which deteriorates production efficiency (see e.g.…”
Section: Introductionmentioning
confidence: 99%